Reversal of ischemic cardiomyopathy with Sca-1+ stem cells modified with multiple growth factors. - Ning Li (Public Library of Science (PLoS), 2014)
Background We hypothesized that bone marrow derived Sca-1+ stem cells (BM Sca-1+) transduced with multiple therapeutic cytokines with diverse effects will induce faster angiomyogenic differentiation in the infarcted myocardium. Methods and results BM Sca-1+ were purified from transgenic male mice expressing GFP. Plasmids encoding for select quartet of growth factors, i.e., human IGF-1, VEGF, SDF-1α and HGF were prepared and used for genetic modification of Sca-1+ cells (GFSca-1+). Scramble transfected cells (ScSca-1+) were used as a control. RT-PCR and western blotting showed significantly higher expression of the growth factors in GFSca-1+. Besides the quartet of the therapeutic growth factors, PCR based growth factor array showed upregulation of multiple angiogenic and prosurvival factors such as Ang-1, Ang-2, MMP9, Cx43, BMP2, BMP5, FGF2, and NGF in GFSca-1+ (p<0.01 vs ScSca-1+). LDH and TUNEL assays showed enhanced survival of GFSca-1+ under lethal anoxia (p<0.01 vs ScSca-1+). MTS assay showed significant increased cell proliferation in GFSca-1+ (p<0.05 vs ScSca-1+). For in vivo study, female mice were grouped to receive the intramyocardial injection of 15 μl DMEM without cells (group-1) or containing 2.5 × 10(5) ScSca-1+ (group-2) or GFSca-1+ (group-3) immediately after coronary artery ligation. As indicated by Sry gene, a higher survival of GFSca-1+ in group-3 on day 4 (2.3 fold higher vs group-2) was observed with massive mobilization of stem and progenitor cells (cKit+, Mdr1+, Cxcr4+ cells). Heart tissue sections immunostained for actinin and Cx43 at 4 weeks post engraftment showed extensive myofiber formation and expression of gap junctions. Immunostaining for vWF showed increased blood vessel density in both peri-infarct and infarct regions in group-3. Infarct size was attenuated and the global heart function was improved in group-3 as compared to group-2. Conclusions Administration of BM Sca-1+ transduced with multiple genes is a novel approach to treat infarcted heart for its regeneration.